WORTHY MICROPROPAGATION PROTOCOLS OF SEVEN CULTIVARS OF POMEGRANATE (PUNICA GRANATUM L.) CULTIVARS IN THE PROVINCE OF DUHOK, KURD ISTAN RIGION OF IRAQ. - Esho, Lara D.; Danial, Gharbia H. (Science Journal of University of Zakho, 2023)
An efficient attempt was conducted to increase the mass production of seven local cultivars of pomegranate (Punica granatum L.) Masafik, Melisse, Radisho, Armishte, Diala, Halapja, and Dwarf pomegranate cultured in the Kurdistan region of Iraq from October 2021 to February 2023. Micropropagation technique was applied using eight combinations of plant growth regulators (PGRs) added to two media (MS and WPM). The results indicated that immersing explants in 70% Ethyl alcohol (EtOH) for (2 minutes) followed by immersion in (2.5%) Sodium Hypochlorite (NaOCl) plus 3 drops of tween 20 for 13 mins. was the more suitable combination for explant sterilization. MS and WPM media salts supplemented together with eight combinations of PGRs were carried out to evaluate the more suitable combination for the initiation stage. The obtained data clarified that the ½ strength of the MS medium (1/2 MS) supplemented with 0.5 BAP plus 0.5 mg/l Kinetin increases the pomegranate explant initiation response percentage. WPM basal medium was the preferred media to be used in the multiplication stage. The impact of different levels and protocols of Cytokinins, Auxins, and Gibberellins were investigated by eight protocols including using BAP, GA3, and adenine sulfate. The outcomes indicated that adding both concentrations of BAP (0.5 and 1.0 mg/l) separately supported by GA3 and adenine sulfate in amounts of (0.3 and 30 mg/l) respectively again were the most suitable protocol that affected the multiplication of regenerated shoots when compared to using BAP alone. Valuable results were found in rooting response after 6 weeks by using ½ strength of MS media along with two levels of Auxins (NAA, and IBA). Moreover, the visual observation records that around 85-90% of rooted cultures were successfully acclimatized by transferring the cultures from in vitro to the ex-vitro environment. Finally, Dwarf cultivars exceed all the other cultivars in studded parameters.